3D Gel Map of Arabidopsis Complex I - Peters, Katrin; Belt, Katharina; Braun, Hans-Peter (Frontiers in Plant Science, 2013)
Complex I has a unique structure in plants and includes extra subunits. Here, we present a novel study to define its protein constituents. Mitochondria were isolated from Arabidopsis thaliana cell cultures, leaves and roots. Subunits of complex I were resolved by 3D blue native (BN)/SDS/SDS-PAGE and identified by mass spectrometry. Overall, 55 distinct proteins were found, 7 of which occur in pairs of isoforms. We present evidence that Arabidopsis complex I consists of 49 distinct types of subunits, 40 of which represent homologues of bovine complex I. The 9 other subunits represent special proteins absent in the animal linage of eukaryotes, most prominently a group of subunits related to bacterial gamma-type carbonic anhydrases. A GelMap (http://www.gelmap.de/arabidopsis-3d-complex-i/) is presented for promoting future complex I research in Arabidosis thaliana.